Pharmacological interventions for the management of anesthesia and sedation in patients with Duchenne muscular dystrophy: a systematic review and meta-analysis - Lian, Xianghong; Jing, Yang; Luo, Ting; Guo, Yixin; Lin, Yunzhu (Frontiers in Medicine, 2025)
BackgroundPatients with duchenne muscular dystrophy (DMD) have an increased risk of complications when they undergo sedation or general anesthesia. However, due to improvements in cardiopulmonary therapies during anesthetic care, patients with DMD are experiencing an unprecedented duration of survival. We performed a systematic analysis to assess the benefits and risks of pharmacological interventions for the management of anesthesia and sedation in DMD patients.MethodsWe included any type of study reporting any drug intervention to manage anesthesia and sedation in participants previously diagnosed with DMD. Our primary outcomes were the onset time, recovery time, and neurodevelopmental disabilities. Seven electronic databases and three clinical trial registry platforms were searched. Data from the eligible studies were combined to calculate pooled risk ratios or standardized mean differences, and some included studies are presented in a narrative synthesis.ResultsForty studies with 196 DMD participants were included in the analysis. Compared with those of the control group, the sensitivity of patients with DMD to neuromuscular blocking agents (NMBAs) may have resulted in a prolonged onset time [MD = −0.96, 95% CI (0.71, 2.60), I2 = 33%, P < 0.0001] and recovery time [MD = 2.22, 95% CI (1.14, 3.30), I2 = 76%, P < 0.0001] from anesthesia. The neuromuscular blocking effects showed a significant age dependence in DMD patients, and the safe use of 2 mg/kg sugammadex to antagonize deep neuromuscular blockade and rapid recovery has been reported. Furthermore, DMD patients are at risk of developing malignant hyperpyrexia with general/inhaled anesthesia, and dantrolene is often used for effective rescue. In addition, general anesthesia and central neuraxial blockade in patients with severe DMD are unsafe because respiratory depression and myocardial complications may occur after the administration of volatile anesthetics and depolarizing muscle relaxants (succinylcholine) during the induction of anesthesia.ConclusionsPatients with DMD are more sensitive to NMBAs with delayed onset times and prolonged recovery times. Precautions for DMD patients should include quantitative neuromuscular monitoring, electrocardiographic monitoring and rapid airway protection throughout anesthesia. Compared with general anesthesia, regional anesthesia may be a relatively safe option.